El método Pikler en la autonomía de los niños del subnivel de preparatoria de la escuela de Educación Básica “Nidia Jaramillo” del Cantón Riobamba - Tipantuña Changoluisa, Lesly Gissela (2024)
This study will reveal the foundations, principles, contributions, perspectives surrounding the “Pikler” method and autonomy in childhood in children. This method provides adequate circumstances for boys and girls so that they can describe the pleasure that their own spontaneous activity brings them, placing special emphasis on the relationship of the accompanying adults to create an environment where children function safely. These adequate conditions are spaces adapted so that boys and girls can play freely and be stimulated, in a large and clear space, that includes objects with which they can interact and that are within the interests and evolutionary needs of children at an individual level where They lay the foundations for cognitive development through experimentation, in addition to developing creativity and being a source of satisfaction. In this way, to describe autonomous activity is to recognize that the infant is a subject of action and not only of reaction from the earliest age. Which implies the operation on the external environment and reciprocal transformation between subject and the environment. In this context, the aim is to analyze how the Pikler method can contribute to the autonomy of children since detailed knowledge of the autonomous activity of children is necessary by providing countless data about the richness and variability of the strategies. individual, in which the child is physically and mentally committed at every moment and at every stage of his development. In this way he constructs himself intellectually, practically and socially, accompanied and supported by his significant adults. Therefore, a bibliographic compilation was carried out that includes contributions from several authors related to the topic in the context of autonomy in Early Childhood. The objective of this research is to reflect on our role as teachers and non-teachers, examining the actions and strategies that can help us